Gain enhancement of a printed leaf shaped UWB antenna using dual FSS layers and experimental study for ground coupling GPR applications. Issue 6 (24th April 2018) - Kundu, Surajit; Chatterjee, Ayan; Jana, Sanjay Kumar; Parui, Susanta Kumar
Abstract: A printed leaf shaped compact (40 mm × 30 mm × 0.8 mm) UWB antenna added with dual frequency selective surfaces (FSS) of dimension 44 mm × 44 mm × 1.6 mm is proposed. The FSS layers having 4 × 4 array in each can provide maximum gain of 8.7 dBi and gain enhancement by 2–4.5 dBi in the antenna bandwidth of 3–14.64 GHz. The proposed design also ensures maximum radiation in the broadside direction with average radiation efficiency of 85%. The antenna bandwidth and group delay responses were measured in close proximity of soil test bed for varying test bed thicknesses. Relative bandwidth of more than 114% with non‐varying group delay response ensure the ability of proposed antenna to work for ground coupling ground penetrating radar applications.